Sleep behaviour and cardiorespiratory fitness in patients after percutaneous coronary intervention during cardiac rehabilitation: protocol for a longitudinal study - Jie Zhou; Jing Wu; Lan Huang; Yiyan Wang; Husheng Li; Xubo Wu (BMJ Open)
Introduction Most patients with coronary heart disease experience sleep disturbances and low cardiorespiratory fitness (CRF), but their relationship during cardiac rehabilitation (CR) is still unclear. This article details a protocol for the study of sleep trajectory in patients with coronary heart disease during CR and the relationship between sleep and CRF. A better understanding of the relationship between sleep and CRF on patient outcomes can improve sleep management strategies.Methods and analysis This is a longitudinal study with a recruitment target of 101 patients after percutaneous cardiac intervention from the Seventh People’s Hospital of Shanghai, China. Data collection will include demographic characteristics, medical history, physical examination, blood sampling, echocardiography and the results of cardiopulmonary exercise tests. The information provided by a 6-min walk test will be used to supplement the CPET. The Pittsburgh Sleep Quality Index will be used to understand the sleep conditions of the participants in the past month. The Patient Health Questionnaire and General Anxiety Disorder Scale will be used to assess depression and anxiety, respectively. All participants will be required to wear an actigraphy on their wrists for 72 hours to monitor objective sleep conditions. This information will be collected four times within 6 months of CR, and patients will be followed up for 1 year. The growth mixture model will be used to analyse the longitudinal sleep data. The generalised estimating equation will be used to examine the associations between sleep and CRF during CR.Ethics and dissemination Ethical approval for this observational longitudinal study was granted by the Shanghai Seventh People’s Hospital Ethics Committee on 23 April 2021 (2021-7th-HIRB-012). Study results will be disseminated in peer-reviewed journal articles.